Dialectics of Classical and Contemporary Ulama Thought in Determining Professional Zakat - Madaniyyah, Fathimah; Azka, Hakim Muttaqie; Ghani, Muhammad Saladin Abdul; Syam, Achmad Malik Achnida; Ismail, Alifian Sya'bani (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study examines the conceptual dynamics and methodological developments of Professional Zakat in classical and contemporary Islamic jurisprudential traditions, which emerged alongside the transformation of modern economic structures and the increasing dominance of professional income as a source of wealth. This study aims to trace the pattern of istinbat among ulama, assess the coherence and discrepancies in the fatwas of religious institutions, and identify the relevance of Professional Zakat as an instrument of wealth distribution within the framework of Islamic fiscal policy. The study employed a qualitative approach, including a literature review, content analysis, and comparative analysis of the works of scholars, institutional fatwas, and academic literature. The results show that most religious institutions accept Professional Zakat at a rate of 2.5% and the nisab of gold, but differ in the determination of the haul and the basis of calculation. Other findings show that integrating Professional Zakat into public policy has the potential to increase economic equality, strengthen the empowerment of mustahik, and enhance the stability of national zakat funds. This study concludes that Professional Zakat has strategic significance in addressing contemporary economic disparities, while demonstrating Islamic jurisprudence's ability to adapt to social change through ijtihad informed by benefits and the modern economic context.